2019
DOI: 10.1101/756239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Stunting and Associated Factors among public Primary School pupils of Bahir Dar city, Ethiopia: School-Based Cross-Sectional Study

Abstract: Background:Stunting is a well-established pupils-health indicator of chronic malnutrition which reliably gives a picture of the past nutritional history and the prevailing environmental and socioeconomic circumstances.Objective: The prevalence of stunting and associated factors among public primary school pupils of Bahir Dar city. Method:A cross-sectional study was carried out from March to June 2019. Data were coded and entered into Epi-Data and exported to SPSS. Then, Anthropometric data were converted into … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…This finding is in agreement with studies reported on the national figures of stunting in Ethiopia (23%) [ 7 ], Dale woreda (25.6%) [ 13 ], Southern Ethiopia (28%) [ 14 ], Uganda's Wakiso District (22.5%) [ 59 ], and Jimma Zone (24.1%) [ 60 ]. Unlike the present study, a lower magnitude of stunting was reported from Ethiopia, such as Southern Ethiopia (28%), Harari (15.8%), Bahir Dar city (15.13%), Babile town (11.2%), Bahir Dar district (18.3%), and Addis Ababa (19.6%) [ 14 , 18 , 55 , 57 , 61 , 62 ], respectively. In contrast, the results are lower than the findings from Gondar town (46.1%) [ 17 ], Arba Minch city (41.9%) [ 24 ], Humbo district (57%) [ 48 ], and Mecha district (37.9%) [ 63 ].…”
Section: Resultscontrasting
confidence: 94%
See 1 more Smart Citation
“…This finding is in agreement with studies reported on the national figures of stunting in Ethiopia (23%) [ 7 ], Dale woreda (25.6%) [ 13 ], Southern Ethiopia (28%) [ 14 ], Uganda's Wakiso District (22.5%) [ 59 ], and Jimma Zone (24.1%) [ 60 ]. Unlike the present study, a lower magnitude of stunting was reported from Ethiopia, such as Southern Ethiopia (28%), Harari (15.8%), Bahir Dar city (15.13%), Babile town (11.2%), Bahir Dar district (18.3%), and Addis Ababa (19.6%) [ 14 , 18 , 55 , 57 , 61 , 62 ], respectively. In contrast, the results are lower than the findings from Gondar town (46.1%) [ 17 ], Arba Minch city (41.9%) [ 24 ], Humbo district (57%) [ 48 ], and Mecha district (37.9%) [ 63 ].…”
Section: Resultscontrasting
confidence: 94%
“…Accordingly, 14–17-year-old children were 48% less [AOR = 0.52; 95% CI: 0.29, 0.95] likely to be stunted than 6–9-year-old children. Numerous other studies revealed that the likelihood of stunting was higher as the child got older [ 13 , 18 , 20 , 27 , 29 , 31 , 32 , 45 , 53 , 54 , 59 , 61 ]. However, in this study, children aged 14–17 years were less likely to be stunted than children aged 6–9 years.…”
Section: Resultsmentioning
confidence: 99%
“…There is closeness between the sample size in this study and that of study in the Myanmar. However, the study showed that the prevalence of stunting was lower than the study done in Addis Ababa, Ethiopia where 17.8% of the school-age children were stunted, 30 Bahir Dar city where 15.13% of the subjects were stunted, 13 Northeast Ethiopia where 14.1% were stunted, 16 North West Ethiopia where 25.5% of school-age children were stunted 25 and urban slums in India where 18.5% of them were stunted. 10 When compared with the study done in Arba Minch where 41.9% of the school-aged children were stunted, 12 and Gondar town where 46.1% were stunted, 6 the prevalence was much lower.…”
Section: Discussionmentioning
confidence: 56%
“…Its short-term effects include mortality and morbidity, whereas its long-term effects include that children do not reach their full developmental potential and would have poor cognitive performance, which in turn has consequences on the country’s economic productivity. 13 Many studies reported the health and physical consequences of child under-nutrition and these may have intergenerational effects. 9 Chronic under-nutrition in childhood is linked to slower cognitive development and serious health impairments later in life that reduces the quality of life of individuals.…”
Section: Introductionmentioning
confidence: 99%